Chapter Quattro viaggi nel tempo, rimanendo in città: cronotopi nella narrativa brasiliana contemporanea - Pincherle, Maria Caterina (Studi e saggi, 2021)
If the concept of time-space, associated to the travel, usually refers to a space-temporal changing from a subject, the aim of this work is to reflect on the possibility to use the same concept for a different process, that involves space and time in other positions regarding to the subject, or else the physical immobility and the research during the time. In the last years some famous Brazilian novels deal not only with actual themes, but they find again their present origins in places cancelled by the urban palimpsest: the senzalas and the slavery live again in the echos of very different works as Becos da memória by Conceição Evaristo (2006), Passageiro do fim do dia by Rubens Figueiredo (2010), and O amor dos homens avulsos by Victor Heringer (2016).